Graphene oxide nanofiltration membrane constructed by charge compensation cross-linking agent and preparation method of graphene oxide nanofiltration membrane
By crosslinking the charge-compensated crosslinking agent with graphene oxide nanosheets, the problem of easy swelling of graphene oxide-based film materials is solved, the selectivity and ion flux of the film are improved, and the efficient salt ion separation and water treatment effects are achieved.
Patent Information
- Application Number
- CN202411968121.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing graphene oxide-based film materials are prone to swelling, resulting in poor structural stability and selectivity and low ion flux.
The charge-compensated crosslinking agent is used to cross-link with graphene oxide nanosheets to improve the permeability and selectivity of the film through sulfonic acid groups, and the stability of the film is improved by thermal cross-linking and ultrasonic treatment.
The separation performance and ion flux of the nanofiltration membrane to salt ions are improved, and the pure water flux can reach 1.8L·m-2·h-1·bar-1, and the retention rate of Na2SO4 exceeds 92.8%.
Smart Images

Figure CN119607908A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a charge compensation cross-linking agent to construct a graphene oxide nanofiltration membrane and a preparation method thereof, belonging to the technical field of cross-linked graphene oxide nanofiltration membrane materials and preparation thereof. Background Art
[0002] Due to the rapid population growth and the booming industry, fresh water resources are becoming increasingly scarce, and people are turning to the ocean for fresh water resources. Membrane separation technology has been widely used in the field of seawater desalination due to its advantages such as high cost-effectiveness, high efficiency and environmental friendliness. Graphene oxide (GO) is rich in surface oxygen-containing functional groups (such as carboxyl, hydroxyl, carbonyl and epoxy groups), and has good hydrophilicity, flexibility and processability. The nanochannels in the GO membrane structure usually exhibit a "size screening effect". At the same time, the carboxyl groups at the edges of the GO nanosheets are deprotonated to produce negative charges. Due to the synergistic effect of the size screening effect and the Donnan effect, the pure GO membrane can strongly repel negatively charged organic molecules and divalent ions, thereby achieving the interception and filtration of organic molecules and salt ions. However, the graphene oxide membrane is easy to swell in aqueous solution, resulting in low selectivity between metal ions. At the same time, the graphene oxide sheets are easy to interact with ions, hindering the transmission of ions, resulting in low ion flux. Therefore, it is necessary to modify and regulate the graphene oxide membrane to improve ion flux and selectivity.
[0003] In order to improve the structural stability of graphene-based membranes, molecular cross-linking strategies are used between layers to accurately and stably control the interlayer structure and separation performance of GO membranes. For example, Carbon Materials Journal (Carbon, 2016, 101, 290-295) reported that different screening of metal ions was achieved by constructing a cross-linked graphene oxide membrane. Under the action of an acid catalyst, the graphene oxide membrane was soaked in a dicarboxylic acid and a diamine solution in turn to achieve cross-linking of the graphene oxide. Compared with pure graphene oxide membranes, the cross-linked graphene oxide membrane prepared by this method has improved screening performance for metal ions of different valence states. However, during the cross-linking process, a large number of oxygen-containing functional groups on the surface of graphene oxide are consumed, and the Donnan effect is weakened, resulting in the obtained membrane material having unsatisfactory separation performance for negatively charged salt ions, and the ion flux is still relatively low, only 10 - 2 mol·m -2 ·h -1 , and the preparation process is complicated and the membrane controllability is poor, which is not conducive to mass production.
[0004] Therefore, it is of great significance to develop a graphene oxide-based membrane material with both interlayer structural stability and high interlayer electronegativity to improve the separation and ion flux of nanofiltration membranes for salt ions. Summary of the invention
[0005] In view of the above problems, the purpose of the present invention is to provide a charge compensation crosslinking agent to construct a graphene oxide nanofiltration membrane and a preparation method thereof, so as to solve the problems that the existing graphene oxide-based membrane materials are easy to swell, resulting in poor structural stability and selectivity of the membrane.
[0006] In view of the above purpose, the present invention provides a charge compensating cross-linking agent to construct a graphene oxide nanofiltration membrane. The nanofiltration membrane is prepared by first cross-linking the charge compensating cross-linking agent and a graphene oxide dispersion, and then diluting, ultrasonicating, and filtering the cross-linked nanosheet dispersion. The charge compensating cross-linking agent contains two groups that can react with graphene oxide and has a sulfonic acid group.
[0007] In one embodiment of the present invention, the charge compensation cross-linking agent is selected from any one of 2,5-diaminobenzenesulfonic acid, 2,4-diaminobenzenesulfonic acid, p-phenylenediamine-2,5-disulfonic acid, and 2,5-diaminobenzene-1,4-disulfonic acid.
[0008] In one embodiment of the present invention, the mass ratio of the graphene oxide to the charge compensating crosslinking agent is 1:0.1 to 1:5, preferably 1:1 to 1:2.
[0009] The present invention also provides a method for preparing the above-mentioned nanofiltration membrane, comprising the following steps:
[0010] (1) Preparation of graphene oxide nanosheet dispersion: flake graphite, concentrated sulfuric acid and concentrated phosphoric acid were mixed and stirred, potassium permanganate was slowly added, and 0.8-3L of deionized water was added after reacting in a water bath at 50°C for 24 hours, and then 10-30mL of 30% hydrogen peroxide was added dropwise until the solution turned golden yellow. After standing overnight, the solution was centrifuged at 3000-3500 r / min for 15-30 minutes, and the total number of centrifugations was 15-20 times. The centrifuged product was washed with 1-5% dilute hydrochloric acid and deionized water to a pH of 5-6, and then dialyzed and dispersed with ultrapure water to obtain a graphene oxide nanosheet dispersion;
[0011] (2) Preparation of a charge compensation crosslinking agent dispersion: dissolving the charge compensation crosslinking agent in ultrapure water, heating and stirring until dissolved, to obtain a charge compensation crosslinking agent dispersion;
[0012] (3) Preparation of a charge-compensated cross-linked graphene oxide nanosheet dispersion: mixing the graphene oxide nanosheet dispersion obtained in step (1) and the charge-compensated cross-linking agent dispersion obtained in step (2), stirring them sufficiently, and then performing thermal cross-linking to obtain a charge-compensated cross-linked graphene oxide nanosheet dispersion;
[0013] (4) Preparation of charge-compensated cross-linked graphene oxide nanofiltration membrane: dilute the charge-compensated cross-linked graphene oxide nanosheet dispersion obtained in step (3), perform ultrasonic treatment, load it on the surface of the macroporous polymer support membrane by vacuum filtration, and obtain the charge-compensated cross-linked graphene oxide nanofiltration membrane after drying.
[0014] In one embodiment of the present invention, in step (1), the size of the flake graphite used in the process of preparing graphene oxide nanosheets is 100-400 mesh, the concentrations of concentrated sulfuric acid and concentrated phosphoric acid are 80%-98% and 80-85% respectively, and the volume ratio of the two is 9:1-7:1.
[0015] In one embodiment of the present invention, in step (1), the mass volume ratio of the flake graphite to concentrated sulfuric acid is 1 g: (100-120) mL.
[0016] In one embodiment of the present invention, in step (1), the concentration of graphene oxide nanosheets in the graphene oxide nanosheet dispersion is 1 to 5 mg / mL.
[0017] In one embodiment of the present invention, in step (2), the concentration of the charge compensating cross-linking agent in the charge compensating cross-linking agent dispersion is 1 to 5 mg / mL.
[0018] In one embodiment of the present invention, in step (2), the charge compensating crosslinker is a crosslinker containing two groups reactive with graphene oxide and having a sulfonic acid group, including at least one of 2,5-diaminobenzenesulfonic acid (DABA), 2,4-diaminobenzenesulfonic acid, p-phenylenediamine-2,5-disulfonic acid, and 2,5-diaminobenzene-1,4-disulfonic acid.
[0019] In one embodiment of the present invention, in step (2), the heating temperature is 60-100° C., the stirring rate is 300-500 r / min, and the heating time is 1-3 h.
[0020] In one embodiment of the present invention, the mixing ratio of the reduced graphene oxide nanosheet dispersion and the charge compensation crosslinking agent dispersion in step (3) is 1:0.1 to 1:5, preferably 1:1 to 1:2, the stirring time is 0.5 to 12 hours, the stirring rate is 300 to 500 r / min, the thermal crosslinking temperature is 60 to 80°C, and the time is 1 to 3 hours.
[0021] In one embodiment of the present invention, in step (4), the concentration range of the charge-compensated cross-linked graphene oxide nanosheet dispersion after dilution is 0.001-0.1 mg / mL, the ultrasonic power is 60-180 W, and the ultrasonic time is 0.2-0.5 h.
[0022] In one embodiment of the present invention, the polymer support membrane in step (4) includes any one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyethersulfone (PES), and mixed cellulose (MCEM) microporous filter membrane.
[0023] In one embodiment of the present invention, the polymer support membrane has a pore size of 0.22 to 0.44 μm and a diameter of 25 to 50 cm.
[0024] In one embodiment of the present invention, the drying time in step (4) is 12 to 24 hours, and the drying temperature is 40 to 60°C.
[0025] The present invention also provides a separation device comprising the charge-compensating cross-linked graphene oxide nanofiltration membrane.
[0026] The present invention also provides application of the charge-compensated cross-linked graphene oxide nanofiltration membrane in the field of water treatment.
[0027] Beneficial effects of the present invention:
[0028] (1) The present invention cross-links graphene oxide nanosheets through a charge compensation cross-linking agent, thereby stabilizing the interlayer spacing of the nanofiltration membrane and compensating for the interlayer electronegativity, thereby improving the selectivity of the membrane.
[0029] (2) The present invention uses a charge compensating crosslinking agent to crosslink the graphene oxide nanosheets. The crosslinking agent has a sulfonic acid group. Due to the hydrophilicity of the sulfonic acid group, the permeability of the crosslinked graphene oxide nanofiltration membrane is improved.
[0030] (3) The nanofiltration membrane prepared by the method of the present invention has excellent membrane permeability and its pure water flux can be as high as 1.8 L·m -2 ·h -1 bar -1 At the same time, the retention rate of Na2SO4 by the prepared nanofiltration membrane exceeded 92.8%. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 These are AFM test images of the charge-compensated cross-linked graphene oxide nanosheets in Example 1, wherein (a) is the AFM test image of the charge-compensated cross-linked graphene oxide nanosheets, and (b) is the height curve of the charge-compensated cross-linked graphene oxide nanosheets after AFM testing.
[0032] Figure 2 The zeta potential diagram of the graphene oxide in Comparative Example 1 and the charge-compensated cross-linked graphene oxide nanosheet dispersion in Example 1.
[0033] Figure 3Scanning electron microscope images of the (a) surface and (b) cross-section of the charge-compensating cross-linked graphene oxide nanofiltration membrane prepared in Example 1. DETAILED DESCRIPTION
[0034] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0035] Example 1
[0036] A method for preparing a graphene oxide nanofiltration membrane constructed with a charge compensation crosslinking agent comprises the following steps:
[0037] (1) Preparation of graphene oxide nanosheet dispersion: 4 g of 325 mesh flake graphite, 480 mL of 98% concentrated sulfuric acid and 54 mL of 85% concentrated phosphoric acid were mixed and stirred, 24 g of potassium permanganate was slowly added, and 800 mL of deionized water was added after reacting in a 50°C water bath for 24 h, followed by dropwise addition of 30% hydrogen peroxide until the solution turned golden yellow, and centrifuged after standing overnight. The centrifuged product was washed with dilute hydrochloric acid and deionized water to pH = 5-6, and after dialysis, dispersed with ultrapure water to obtain a graphene oxide nanosheet dispersion with a concentration of 1 mg / mL.
[0038] (2) Preparation of charge compensation crosslinker dispersion: 0.021 mmol 2,5-diaminobenzenesulfonic acid (4 mg) was dissolved in 4 mL ultrapure water, and then dissolved at a rotation speed of 400 r / min and a temperature of 80° C. for 3 h to obtain a charge compensation crosslinker dispersion with a concentration of 1 mg / mL.
[0039] (3) Preparing a charge-compensating cross-linked graphene oxide nanosheet dispersion: The graphene oxide nanosheet dispersion obtained in step (1) and the charge-compensating cross-linking agent dispersion obtained in step (2) were mixed at a volume ratio of 1:1, and stirred at 400 r / min for 30 min to make the dispersions uniformly mixed. Then, the cross-linking reaction was carried out at a speed of 400 r / min and a temperature of 80° C. for 3 h.
[0040] (4) Preparation of charge-compensated cross-linked graphene oxide nanofiltration membrane: 2 mL of the charge-compensated cross-linked graphene oxide nanosheet dispersion obtained in step (3) was diluted to 200 mL of solution, and after ultrasonication at 180 W for 0.5 h, the uniformly mixed dispersion was filtered on a PES microporous filter membrane with a pore size of 0.22 μm and a diameter of 50 mm by vacuum assisted filtration, and dried at 45° C. for 24 h to obtain a charge-compensated cross-linked graphene oxide nanofiltration membrane, named DABA-GO membrane.
[0041] The separation performance of the membrane was tested using a cross-flow filtration device, and its pure water flux was 1.8 L·m -2 ·h -1 bar -1 The retention rate of Na2SO4 is 92.8%.
[0042] Performance characterization of charge-compensated cross-linked graphene oxide nanofiltration membrane
[0043] The charge compensation cross-linked graphene oxide nanofiltration membrane prepared in Example 1 was characterized, and the results are shown in Figures 1 to 3 .from Figure 1 It can be seen that the prepared charge-compensated cross-linked graphene oxide nanosheets present an obvious two-dimensional structure with a high and low surface and a thickness of 10 to 14 nm. The above results indicate that GO and DABA are successfully cross-linked.
[0044] from Figure 2 It can be seen that the Zeta potential value of the charge-compensated cross-linked graphene oxide nanosheet dispersion is more negative than that of the graphene oxide dispersion, showing stronger electronegativity.
[0045] from Figure 3 It can be seen that the membrane surface is dense and complete without defects, and the cross-sectional thickness is about 225nm, which helps the membrane to retain salt ions.
[0046] Example 2
[0047] The difference between Example 2 and Example 1 is that the added amount of 2,5-diaminobenzenesulfonic acid is 2 mg, and a charge compensation crosslinker dispersion having a GO:DABA mass ratio of 1:0.5 is obtained.
[0048] The separation performance of the membrane was tested using a cross-flow filtration device, and its pure water flux was 3.6 L·m -2 ·h -1 bar -1 The retention rate of Na2SO4 is 87.8%.
[0049] Example 3
[0050] The difference between Example 3 and Example 1 is that the added amount of 2,5-diaminobenzenesulfonic acid is 6 mg, and a charge compensation crosslinker dispersion having a GO:DABA mass ratio of 1:1:5 is obtained.
[0051] The separation performance of the membrane was tested using a cross-flow filtration device, and its pure water flux was 1.4 L·m -2 ·h -1 bar -1 The retention rate of Na2SO4 is 91.3%.
[0052] Example 4
[0053] The difference between Example 4 and Example 1 is that the added amount of 2,5-diaminobenzenesulfonic acid is 8 mg, and a charge compensation crosslinker dispersion having a GO:DABA mass ratio of 1:2 is obtained.
[0054] The separation performance of the membrane was tested using a cross-flow filtration device, and its pure water flux was 1.2 L·m -2 ·h -1 bar -1 The retention rate of Na2SO4 is 92.3%.
[0055] It can be seen from Examples 1 to 4 that as the mass ratio of the charge-compensating crosslinking agent 2,5-diaminobenzenesulfonic acid crosslinking agent to the graphene oxide nanosheets increases, the interception performance of the composite membrane for Na2SO4 gradually increases and then stabilizes, but the pure water flux gradually decreases. When the mass ratio of graphene oxide to the charge-compensating crosslinking agent is 1:1, the composite membrane has better separation performance.
[0056] Example 5
[0057] The difference between Example 5 and Example 1 is that the added amount of 2,4-diaminobenzenesulfonic acid is 4 mg, and a charge compensation crosslinker dispersion having a mass ratio of GO to 2,4-diaminobenzenesulfonic acid of 1:1 is obtained.
[0058] The separation performance of the membrane was tested using a cross-flow filtration device, and its pure water flux was 0.9 L·m -2 ·h -1 bar -1 The retention rate of Na2SO4 is 94.4%.
[0059] It can be seen from Examples 1 and 5 that, compared with 2,5-diaminobenzenesulfonic acid, the composite membrane uses 2,4-diaminobenzenesulfonic acid, in which the distance between diamine molecules is closer, to improve the retention performance of Na2SO4, but the pure water flux is relatively reduced.
[0060] Comparative Example 1:
[0061] The difference between Comparative Example 1 and Example 1 is that steps (2) and (3) are omitted, and the graphene oxide nanosheet dispersion of step (1) is directly diluted to 200 mL of solution. After ultrasonication at a power of 180 W for 0.5 h, the uniformly mixed dispersion is filtered on a PES microporous filter membrane with a pore size of 0.22 μm and a diameter of 50 mm by vacuum assisted filtration, and dried at 45° C. for 24 h to obtain a pure graphene oxide nanofiltration membrane, named GO membrane.
[0062] The separation performance of the membrane was tested using a cross-flow filtration device, and its pure water flux was 6.9 L·m -2 ·h -1 bar -1The retention rate of Na2SO4 is 68.2%.
[0063] Comparative Example 2:
[0064] Graphene oxide nanosheets are dispersed in deionized water to obtain a dispersion of graphene oxide nanosheets with a concentration of 1 mg / mL. The preparation method of graphene oxide nanosheets is the same as that in Example 1. The graphene oxide dispersion is hydrothermally reduced at a speed of 400 r / min and a temperature of 80°C for 3 hours. 1 ml of the hydrothermally reduced graphene oxide nanosheet dispersion is taken and diluted into 200 mL of solution. After ultrasonication at a power of 180 W for 0.5 h, the uniformly mixed dispersion is filtered on a PES microporous filter membrane with a pore size of 0.22 μm and a diameter of 50 mm by vacuum assisted filtration, and dried at 45°C for 24 hours to obtain a reduced graphene oxide nanofiltration membrane, named rGO membrane. The separation performance of the membrane was tested using a cross-flow filtration device, and its pure water flux was 5.1 L·m -2 ·h -1 bar -1 The retention rate of Na2SO4 is 80.7%.
[0065] Comparative Example 3:
[0066] The difference between Comparative Example 3 and Example 1 is that the cross-linking agent in step (2) is replaced by p-phenylenediamine, and the nanofiltration membrane is prepared according to the following scheme.
[0067] (1) Preparing a graphene oxide dispersion: dilute and disperse graphene oxide nanosheets in deionized water to obtain a graphene oxide nanosheet dispersion with a concentration of 1 mg / mL. The preparation method of the graphene oxide nanosheets is the same as that in Example 1.
[0068] (2) Preparation of p-phenylenediamine crosslinking agent dispersion: 0.021 mmol p-phenylenediamine (2.3 mg) was dissolved in 4 mL of ultrapure water, and then dissolved at a rotation speed of 400 r / min and a temperature of 80° C. for 3 h to obtain a p-phenylenediamine crosslinking agent dispersion with a concentration of 2 mg / mL.
[0069] (3) Preparation of p-phenylenediamine cross-linked graphene oxide nanosheet dispersion: The graphene oxide nanosheet dispersion obtained in step (1) and the p-phenylenediamine cross-linking agent dispersion obtained in step (2) were mixed at a volume ratio of 1:1, and stirred at 400 r / min for 30 min to make the dispersions uniformly mixed. Then, the cross-linking reaction was carried out at a speed of 400 r / min and a temperature of 80° C. for 3 h.
[0070] (4) Preparation of p-phenylenediamine cross-linked graphene oxide nanofiltration membrane: 2 ml of the p-phenylenediamine cross-linked graphene oxide nanosheet dispersion obtained in step (3) was diluted to 200 mL of solution, and after ultrasonication at a power of 180 W for 0.5 h, the uniformly mixed dispersion was filtered onto a PES microporous filter membrane with a pore size of 0.22 μm and a diameter of 50 mm by vacuum assisted filtration, and dried at 45° C. for 24 h to obtain a p-phenylenediamine cross-linked graphene oxide nanofiltration membrane, named PDD-GO membrane.
[0071] The separation performance of the membrane was tested using a cross-flow filtration device, and its pure water flux was 0.9 L·m -2 ·h -1 bar -1 The retention rate of Na2SO4 is 61.6%.
[0072] Comparative Example 5:
[0073] The difference between Comparative Example 5 and Example 1 is that the added amount of 2,5-diaminobenzenesulfonic acid is 40 mg, and a charge compensation crosslinker dispersion having a GO:DABA mass ratio of 1:10 is obtained.
[0074] The separation performance of the membrane was tested using a cross-flow filtration device, and its pure water flux was 1.5 L·m -2 ·h -1 bar -1 The retention rate of Na2SO4 is 85.9%.
[0075] Comparative Example 6:
[0076] The difference between Comparative Example 6 and Example 1 is that the temperature for cross-linking 2,5-diaminobenzenesulfonic acid and GO nanosheets in step (3) is 40°C.
[0077] The separation performance of the membrane was tested using a cross-flow filtration device, and its pure water flux was 5.2 L·m -2 ·h -1 bar -1 The retention rate of Na2SO4 is 78.3%.
[0078] Comparative Example 7:
[0079] The difference between Comparative Example 7 and Example 1 is that in step (4), the ultrasonic time is 1 h.
[0080] The separation performance of the membrane was tested using a cross-flow filtration device, and its pure water flux was 2.7 L·m -2 ·h -1 bar -1 The retention rate of Na2SO4 is 88.5%.
[0081] Comparative Example 8
[0082] The difference between Comparative Example 8 and Example 1 is that in step (1), the concentration of the graphene oxide nanosheet dispersion is 8 mg / mL;
[0083] In step (2), the amount of 2,5-diaminobenzenesulfonic acid added is 32 mg, and the concentration of the charge compensating crosslinking agent dispersion is 8 mg / mL; in step (4), the volume of the charge compensating crosslinking agent dispersion dispersed in 200 mL of ultrapure water is 0.25 mL.
[0084] The separation performance of the membrane was tested using a cross-flow filtration device, and its pure water flux was 16.7 L·m -2 ·h -1 bar -1 The retention rate of Na2SO4 is 34.7%.
Claims
1. A method for preparing a graphene oxide nanofiltration membrane constructed with a charge compensation crosslinking agent, characterized in that: The following steps are involved: (1) Preparation of graphene oxide nanosheet dispersion: flake graphite, concentrated sulfuric acid and concentrated phosphoric acid were mixed and stirred, potassium permanganate was slowly added, and 0.8-3L of deionized water was added after reacting in a water bath at 50°C for 24 hours, and then 10-30mL of 30% hydrogen peroxide was added dropwise until the solution turned golden yellow. After standing overnight, the solution was centrifuged at 3000-3500 r / min for 15-30 minutes, and the total number of centrifugations was 15-20 times. The centrifuged product was washed with 1-5% dilute hydrochloric acid and deionized water to a pH of 5-6, and then dialyzed and dispersed with ultrapure water to obtain a graphene oxide nanosheet dispersion; (2) Preparation of a charge compensation crosslinking agent dispersion: dissolving the charge compensation crosslinking agent in ultrapure water, heating and stirring until dissolved, to obtain a charge compensation crosslinking agent dispersion; (3) Preparation of a charge-compensated cross-linked graphene oxide nanosheet dispersion: mixing the graphene oxide nanosheet dispersion obtained in step (1) and the charge-compensated cross-linking agent dispersion obtained in step (2), stirring them sufficiently, and then performing thermal cross-linking to obtain a charge-compensated cross-linked graphene oxide nanosheet dispersion; (4) Preparation of charge-compensated cross-linked graphene oxide nanofiltration membrane: dilute the charge-compensated cross-linked graphene oxide nanosheet dispersion obtained in step (3), perform ultrasonic treatment, load it on the surface of the macroporous polymer support membrane by vacuum filtration, and obtain the charge-compensated cross-linked graphene oxide nanofiltration membrane after drying.
2. The preparation method according to claim 1, characterized in that: In step (1), the size of the flake graphite used in the process of preparing graphene oxide nanosheets is 100-400 meshes, the concentrations of concentrated sulfuric acid and concentrated phosphoric acid are 80%-98% and 80-85% respectively, the volume ratio of the two is 9:1-7:1, the mass volume ratio of the flake graphite to the concentrated sulfuric acid is 1g:(100-120)mL, and the concentration of the graphene oxide nanosheets in the graphene oxide nanosheet dispersion is 1-5mg / mL.
3. The preparation method according to claim 1, characterized in that: In step (2), the concentration of the charge compensating cross-linking agent in the charge compensating cross-linking agent dispersion is 1 to 5 mg / mL.
4. The preparation method according to claim 1, characterized in that: In step (2), the charge compensation cross-linking agent is a cross-linking agent containing two groups that can react with graphene oxide and having a sulfonic acid group, including at least one of 2,5-diaminobenzenesulfonic acid, 2,4-diaminobenzenesulfonic acid, p-phenylenediamine-2,5-disulfonic acid, and 2,5-diaminobenzene-1,4-disulfonic acid. The heating temperature is 60-100° C., the stirring rate is 300-500 r / min, and the heating time is 1-3 h.
5. The preparation method according to claim 1, characterized in that: The mixing ratio of the reduced graphene oxide nanosheet dispersion and the charge compensation crosslinking agent dispersion in step (3) is 1:0.1 to 1:5, the stirring time is 0.5 to 12 hours, the stirring rate is 300 to 500 r / min, the thermal crosslinking temperature is 60 to 80° C., and the time is 1 to 3 hours.
6. The preparation method according to claim 1, characterized in that: In step (4), the concentration range of the charge-compensated cross-linked graphene oxide nanosheet dispersion after dilution is 0.001 to 0.1 mg / mL, the ultrasonic power is 60 to 180 W, and the ultrasonic time is 0.2 to 0.5 h.
7. The preparation method according to claim 1, characterized in that: The polymer support membrane in step (4) includes any one of polyvinylidene fluoride, polytetrafluoroethylene, polyethersulfone, and mixed cellulose microporous filter membrane. The pore size of the polymer support membrane is 0.22 to 0.44 μm, the diameter is 25 to 50 cm, the drying time is 12 to 24 hours, and the drying temperature is 40 to 60°C.
8. A charge-compensated cross-linked graphene oxide nanofiltration membrane prepared according to the preparation method according to any one of claims 1 to 7.
9. A separation device comprising the charge-compensated cross-linked graphene oxide nanofiltration membrane according to claim 8.
10. Use of the charge-compensated cross-linked graphene oxide nanofiltration membrane according to claim 8 in the field of water treatment.
Citation Information
Patent Citations
Water purification
CN107810049A
Selectively permeable graphene oxide membrane
CN110573240A
Polyvinyl alcohol-modified graphene oxide nano-composite aqueous dispersion and preparation method thereof
CN113929927A
Preparation method and application of two-dimensional ion pair membrane
CN115608175A
Graphene based filter
US20130270188A1
Cited By
Composite separation membrane as well as preparation method and application thereof
CN120115023A